Balanced Modulator Chip Multipliers Three Signals - Malvar, Henrique S.; Malvar, Henrique S. (Electronics, 1979)
This circuit expands the capabilities of a balanced analog signal multiplier by adding a third single-polarity input, which can be used as a gain control, for example. The voltage-to-current converter connecting the third input to the modulator chip ensures high linearity for the third input gain control.